China Urbanizes : Consequences, Strategies, and Policies - Yusuf, Shahid (Washington, DC : World Bank, 2012)
Rural-urban migration is playing an increasingly important role in shaping the economic and demographic landscape of Chinese cities. Over the past two decades, China has transformed itself from a relatively immobile society to one in which more than 10 percent of the population are migrants. China's mobility rate is still low compared with that of advanced industrial economies, the sheer size of the migrant flows and their dramatic economic and social consequences have already profoundly affected economic growth and urban development. Looking ahead, decision makers at all levels will need to craft policies that address issues of migration and rural-urban migrants issues that are hotly debated among scholars, Chinese policy makers, and others. This report presents recent findings that describe migration patterns and changes since the 1980s.